Safety profile of laser-assisted drug delivery of vitamin C, E, and ferulic acid serum following ablative fractional resurfacing: A retrospective chart review. (17th November 2021) - Johnson, Hadley; Kazemi, Tiana; Farah, Ronda S.
ABSTRACT: Objectives: The topical application of a combination Vitamin C, Vitamin E, and Ferulic acid serum following ablative fractional resurfacing has been reported to shorten post-procedure downtime and improve wound healing. However, transcutaneous drug delivery of cosmeceuticals initially meant for topical application have also been shown to have unintended side effects. The objective of our study was to report safety data from our single academic center experience consisting of patients treated with topical application of a vitamin C-containing cosmeceutical immediately following fractional ablative CO2 laser treatment with a focus on reportable side effects. Methods: A retrospective chart review of all patients at the University of Minnesota M Health Cosmetic Center who had fractional ablative CO2 (10, 600 nm) laser procedure for any diagnosis followed by immediate one-time application of a combination serum containing 15% Vitamin C, 1% Vitamin E, and 0.5% Ferulic acid (C E Ferulic®, SkinCeuticals Inc., New York, NY) from Jan 1, 2015 to Dec 31, 2018 was performed. Pediatric and research opt-out patients were excluded. The medical records of these patients were manually reviewed for the following: age, sex, diagnosis, location, after-care instructions, antiviral and/or antibacterial prophylaxis use, and documentation of post-procedure side effects. Results: Thirty-three patients, encompassing a total of 45 treatment encounters, met inclusion criteria. There were ten cases of expected side effects: erythema (6), erythema with tenderness (1), erythema with mild bumpiness (1), skin peeling with pattern marking (1), and pain with slight bleeding (1). These were attributed to the normal post-procedure course and resolved without complications. There were no reported side effects related to the topical application of Vitamin C, Vitamin E, and Ferulic acid serum. Conclusions: The topical application of a Vitamin C, Vitamin E, and Ferulic acid serum immediately following fractional ablative CO2 laser therapy did not result in associated complications. However, these results may not be generalizable to longer application courses beyond the immediate post-procedure time period, nor to other cosmeceutical formulations. More studies examining the safety profile of topical cosmeceutical serums in laser-assisted drug delivery are needed.